1986
DOI: 10.1007/bf01299818
|View full text |Cite
|
Sign up to set email alerts
|

Visceral myopathy of the colon mimicking Hirschsprung's disease

Abstract: A 51-year-old man presented with a history and physical findings consistent with adult Hirschsprung's disease. An inadvertent transmural rectal biopsy led to the unexpected diagnosis of a visceral myopathy, a diagnosis which was confirmed by subsequent colectomy. The pathological findings are reviewed, and the potential use of transmural rectal biopsy in the diagnosis of smooth muscle disorders of the colon is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…99]. Full thickness rectal biopsies may have some add ed efficacy as reported in 1 case of a visceral myopathy mimicking Hirschsprung's disease [100]. 174 Veme/Sninsky Chronic Intestinal Pseudo-Obstruction …”
Section: Antroduodenalmentioning
confidence: 99%
“…99]. Full thickness rectal biopsies may have some add ed efficacy as reported in 1 case of a visceral myopathy mimicking Hirschsprung's disease [100]. 174 Veme/Sninsky Chronic Intestinal Pseudo-Obstruction …”
Section: Antroduodenalmentioning
confidence: 99%
“…Careful studies of full-thickness samples of the GJ wall have revealed a variety of pathologies to underlie the syndrome of ClIP. The vast majority of ClIPs have identifiable abnormalities within intestinal smooth muscle layers or intrinsic neurons (12)(13)(14)(15); moreover, both systems may be affected by the same disease (16).…”
mentioning
confidence: 99%